A pup called trouble - Pyron, Bobbie (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
When a coyote pup named Trouble stows away in the back of a truck, he ends up in the heart of New York City, and must choose between the risks of being caught and the dangers of a long journey home.
Keywords: Coyotes -- Fiction; Adventure and adventurers -- Fiction; Central Park (New York, N.Y.) -- Fiction; New York (N.Y.) -- Fiction